Crack detection in beams with different boundary conditions - Barbieri N. (2014)
In this paper the damage in clamped-free, clamped-clamped and free-free beam are analyzed considering samples without and with structural modifications. The procedure is extended to analysis of damage in a sandwich beam. The damage location is investigated by the use of the bispectrum and wavelet analysis. The mathematical models are obtained using 2D elasticity theory and the Finite Element Method (FEM). The numerical and experimental data are approximated using the Particle Swarm Optimizer (PSO) method and this way is possible to adjust the localization and the severity of the damage. The experimental data are obtained through accelerometers placed along the sample. The system is excited using impact hammer.